2019
DOI: 10.1016/j.jad.2019.08.052
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal depression among mothers in a South African birth cohort study: Trajectories from pregnancy to 18 months postpartum

Abstract: Background: Perinatal depression affects 21–50% of women in South Africa and poses significant health risks to mothers and children. Trajectories of depressive symptoms change over time and have not been well characterized during the perinatal period in low and middle-income countries. Methods: Data from women enrolled in a population-based birth cohort study in Paarl, South Africa with at least 3 depression measures from pregnancy through 18 months postpartum (N=831) were analyzed. Depressive symptoms were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 48 publications
4
41
1
Order By: Relevance
“…The results of the current study showed higher levels at nine, 12 and 17 months after childbirth, and a doubled risk of depression symptoms at 9-12 months and at 17-21 compared to the other times. This is an interesting find, which adds to the growing evidence of maternal depression occurring not only in the first few months after birth [6,[38][39][40]. Both Kothari et al [6] and Gjerdingen et al [38] found high levels of depression symptoms in the first month.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The results of the current study showed higher levels at nine, 12 and 17 months after childbirth, and a doubled risk of depression symptoms at 9-12 months and at 17-21 compared to the other times. This is an interesting find, which adds to the growing evidence of maternal depression occurring not only in the first few months after birth [6,[38][39][40]. Both Kothari et al [6] and Gjerdingen et al [38] found high levels of depression symptoms in the first month.…”
Section: Discussionsupporting
confidence: 57%
“…Gjerdingen et al [38] could not explain the second peak at nine months. Different trajectories regarding onset and development have been identified [39,40]. In a study from Brazil, about one in 10 showed an initial high level and then decreasing, whereas a similar proportion showed an increase in symptoms of depression up until 24 months (which was how long the study measured the mothers) [39].…”
Section: Introductionmentioning
confidence: 99%
“…Research on postpartum women has identified a wide range of clinical conditions that may impact on their well-being following childbirth: from the more common baby blues, that is a physiological and transitory condition (Rezaie-Keikhaie et al, 2020), to more severe conditions, such as anxiety and mood disorders, puerperal psychosis, and post-traumatic stress disorder (Paulson and Bazemore, 2010;Meltzer-Brody et al, 2017;Mohamied, 2019;Pellowski et al, 2019). Specifically, the prevalence of anxiety spectrum disorders has been found to be around 10% (15% for anxiety symptoms) (Dennis et al, 2017), whilst depressive symptoms have been reported in 10-22% of mothers, depending on the different cut-off scores used in the studies (Zaers et al, 2008;Pampaka et al, 2018;Sunnqvist et al, 2018).…”
Section: Psychological Well-being Of Postpartum Womenmentioning
confidence: 99%
“…The birth of a child represents a critical experience in a woman's life, entailing several changes both at the individual (physical and psychological) and interpersonal level (Lawrence et al, 2008;Guzzo and Hayford, 2020). This experience may negatively impact on individual well-being, leading to several forms of distress and/or diseases including anxiety, mood and post-traumatic stress disorders (Paulson and Bazemore, 2010;Meltzer-Brody et al, 2017;Mohamied, 2019;Pellowski et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…While perinatal depression is common among diverse groups of women in many countries around the world [ 2 , 3 , 4 , 5 ], women in low- and middle-income countries experience a higher burden of this illness [ 6 ]. Recent studies have demonstrated that women in low- and middle-income countries have a perinatal depression rate of up to 48.5% [ 7 , 8 , 9 , 10 , 11 ]. These figures are alarming as the rates reported in high-income countries are much lower, ranging from 6.5% to 12.9% during the perinatal period [ 6 , 12 ].…”
Section: Introductionmentioning
confidence: 99%